INFORMED CONSENT DALAM PERLINDUNGAN DOKTER YANG MELAKUKAN EUTHANASIA - Listyaningrum, Novita (Jurnal Advokasi, 2016)
Until now Indonesia has not specifically regulating about euthanasia yet. Euthanasia concept is still become a subject for debate among law experts, among them are some who agree and disagree on performing euthanasia. The agree party expressed their opinion that every person has own right to life and also right to end his own life immediately for humanitarian reasons, with condition that no possibility to recover even for keep a life, so they may ask for euthanasia. While the disagree party that not allow euthanasia, they are have an argument that every person has no right to end his own life at all because life and death is absolutely authority of Allah Subhanahu wa Taala, that can not be interrupted. Therefore it is necessary to make a deep study about euthanasia from medical aspect with informed consent support that give protection to doctor who performing euthanasia.